2017
DOI: 10.3389/fpsyg.2017.00738
|View full text |Cite
|
Sign up to set email alerts
|

Social Saliency of the Cue Slows Attention Shifts

Abstract: Eye gaze is a powerful cue that indicates where another person’s attention is directed in the environment. Seeing another person’s eye gaze shift spontaneously and reflexively elicits a shift of one’s own attention to the same region in space. Here, we investigated whether reallocation of attention in the direction of eye gaze is modulated by personal familiarity with faces. On the one hand, the eye gaze of a close friend should be more effective in redirecting our attention as compared to the eye gaze of a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Behavioral evidence suggests that personally familiar faces are processed faster 20 23 , 51 , and require fewer attentional resources 19 . On the other hand, we also have shown that familiar faces, relative to unfamiliar faces, slow down shifts of attention away from the face, suggesting they hold attention 52 . We found reduced BOLD activation to personally familiar faces only in the IPL 53 , 54 , while areas of the core and extended systems showed stronger responses.…”
Section: Discussionmentioning
confidence: 57%
“…Behavioral evidence suggests that personally familiar faces are processed faster 20 23 , 51 , and require fewer attentional resources 19 . On the other hand, we also have shown that familiar faces, relative to unfamiliar faces, slow down shifts of attention away from the face, suggesting they hold attention 52 . We found reduced BOLD activation to personally familiar faces only in the IPL 53 , 54 , while areas of the core and extended systems showed stronger responses.…”
Section: Discussionmentioning
confidence: 57%
“…Much of the effort focused on others' gaze direction and its impact on spatial orienting. It showed that other's gaze direction can reallocate our attention not always in an automatic, bottom-up way, determined by its sole physical saliency, but also in a voluntary, top-down way, driven by both the observer's social relevance and the subject's goals (Koval et al, 2005;Birmingham and Kingstone, 2009;Greene et al, 2009;Chauhan et al, 2017;Atkinson et al, 2018). In this eye gaze domain too, familiar peers may have special effects (Chauhan et al, 2017).…”
Section: Social Attention Literaturementioning
confidence: 99%
“…We chose familiar peers based on evidence that they are more effective social facilitation triggers than strangers. This includes the evidence from the attention literature evoked above (Fareri et al, 2012;Chauhan et al, 2017), plus similar evidence from primatology (Wechkin, 1970) and social psychology (Herman, 2015). We also chose familiar peers because of their omnipresence at school or work, the two daily life situations that could benefit most from novel findings in social facilitation research.…”
Section: Social Attention Literaturementioning
confidence: 99%
“…Learning associated with repeated personal interactions modifies the representation of these faces, suggesting that personal familiarity affects face-processing areas well after developmental critical periods (Arcaro et al, 2017; Livingstone et al, 2017). We hypothesize that these differences may be one of the mechanisms that underlies the known behavioral advantages for perception of personally familiar faces (Burton et al, 1999; Gobbini and Haxby, 2007; Gobbini, 2010; Gobbini et al, 2013; Visconti di Oleggio Castello et al, 2014, 2017b; Ramon et al, 2015; Visconti di Oleggio Castello and Gobbini, 2015; Chauhan et al, 2017; Ramon and Gobbini, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Faces, and personally familiar faces in particular, are important social stimuli whose correct detection and processing affects social behavior (Brothers, 2002; Gobbini and Haxby, 2007). Behavioral experiments from our lab have shown that personally familiar faces break through faster in a continuous flash suppression paradigm (Gobbini et al, 2013), and hold attention more strongly than unfamiliar faces do in a Posner cueing paradigm (Chauhan et al, 2017). These results show that familiar faces differ not only at the level of representations, but also in allocation of attention.…”
Section: Discussionmentioning
confidence: 99%